Negosiasi Dakwah Digital: Kontinuitas dan Transformasi di Kalangan Ulama NU di Lombok - Fathurrahman, Fathurrahman; Wildan, Muhammad Dimas Hidayatullah (JOM, 2026)
The rapid development of information technology and the Covid-19 pandemic have significantly transformed the landscape of Islamic preaching (da'wah), prompting traditional religious authorities to adapt their strategies. This study examines how Nahdlatul Ulama (NU) ulama in Lombok respond to these changes. Employing a qualitative field research approach, data were collected through direct observation of preaching activities and the digital engagement of NU ulama. The analysis draws on Campbell’s framework in Who’s Got the Power?, which explores the shifting dynamics of religious authority in the digital era. The findings indicate that NU ulama adopt a hybrid preaching strategy. They actively utilize social media platforms through livestream preaching and contextual religious content, while simultaneously maintaining conventional religious gatherings such as majelis taklim held in mosques, pesantren halls, and neighborhood prayer rooms. Theoretically, this study demonstrates that digital media does not replace traditional religious authority but instead reinforces embodied and community-based forms of Islamic knowledge and preaching.